2021
DOI: 10.1051/e3sconf/202128702010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial performance of menthol and menthol-based deep eutectic solvents as potential future antibiotic

Abstract: Triggered by the strong antimicrobial activities of menthol and various fatty acids, eutectic mixtures based on the components are developed, producing new solvents that have possibilities to become a new antibiotic. This study aims to provide an insight into the antimicrobial activities of the new deep eutectic solvents (DESs) developed. Menthol-based DES combined with fatty acids, namely propionic acid, butanoic acid, hexanoic acid, octanoic acid, decanoic acid, and levulinic acid, were successfully obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, choline chloride (ChCl) and urea are used as DES precursors for the chemical modification of silica particles based on DES (Tang et al, 2014;Gu et al, 2015). Some previous studies have also reported the use of DESs as antimicrobial agents (Garcia-Arguelles et al, 2013;Wikene et al, 2017;Al-Akayleh et al, 2022;Azmi et al, 2021), antioxidants (Inayat et al, 2023) , and for environmental remediation (Kaur et al, 2021;Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, choline chloride (ChCl) and urea are used as DES precursors for the chemical modification of silica particles based on DES (Tang et al, 2014;Gu et al, 2015). Some previous studies have also reported the use of DESs as antimicrobial agents (Garcia-Arguelles et al, 2013;Wikene et al, 2017;Al-Akayleh et al, 2022;Azmi et al, 2021), antioxidants (Inayat et al, 2023) , and for environmental remediation (Kaur et al, 2021;Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, type V DESs have been introduced as alternatives to water-immiscible hazardous organic solvents . In particular, research has been conducted on menthol-based type V DESs as liquid–liquid extraction solvents, and 17 DESs including thymol, decanoic acid, , and menthol, , have been suggested as promising candidates for replacing toxic organic solvents currently used for preparing pharmaceutical drugs . Another study reported that combining DES with nontoxic levulinic acid , could produce a reliable extraction solvent that can replace volatile organic extraction solvents.…”
Section: Introductionmentioning
confidence: 99%
“… 11 DESs containing menthol and short chain fatty acids, including propionic acid, butanoic acid, hexanoic acid, and levulinic acid, also exhibit antimicrobial activities. 12 Deep eutectic mixtures of drugs have also been shown to improve pharmacological action. For example, the deep eutectic mixture of limonene and ibuprofen (IBU) inhibited HT29 proliferation and increased the anti-inflammatory action of IBU, both of which are essential in anti-cancer therapy.…”
Section: Introductionmentioning
confidence: 99%